2015
DOI: 10.1016/j.autrev.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The European Registry on Obstetric Antiphospholipid Syndrome (EUROAPS): A survey of 247 consecutive cases

Abstract: OAPS shows differential characteristics than classical APS. All laboratory test categories are needed to avoid false-negative diagnoses. In some cases, complement levels could act as a serological marker. OAPS has very good foetal-maternal outcomes when treated. Thrombosis and progression to SLE in mothers with OAPS are scarce compared with "classical APS", suggesting that they have different aPL-mediated pathogenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 40 publications
5
76
0
1
Order By: Relevance
“…The current treatment of all pregnant APS patients encompasses low-molecular weight heparin (LMWH) and low-dose aspirin (LDASA); thanks to this combo regimen, 78% of women deliver a viable infant [28]. However, it is increasingly acknowledged that aPLpositive women might be clustered in two clinical subsets potentially benefitting from different therapeutic approaches.…”
Section: Obstetric Antiphospholipid Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The current treatment of all pregnant APS patients encompasses low-molecular weight heparin (LMWH) and low-dose aspirin (LDASA); thanks to this combo regimen, 78% of women deliver a viable infant [28]. However, it is increasingly acknowledged that aPLpositive women might be clustered in two clinical subsets potentially benefitting from different therapeutic approaches.…”
Section: Obstetric Antiphospholipid Syndromementioning
confidence: 99%
“…Indeed, women with high-risk triple aPL-positivity usually experience severe late pregnancy complications, while women with a history of recurrent early miscarriages tend to carry low-risk aPL profile, such as a low-titre (below the threshold considered in the updated APS classification criteria) or single positive aPL test. Surely single aPL-positivity should not be neglected in the context of obstetric APS: in the European registry, 67% of included women had a single aPL-positivity [28]. Recent data suggest that the standard regimen might be effective in low-titre aPL-positive early miscarriages, but might be not be enough in the management of late events associated with high-titre aPLs [29 & ,30].…”
Section: Obstetric Antiphospholipid Syndromementioning
confidence: 99%
“…Alijotas et al, in the European Registry on Obstetric Antiphospholipid Syndrome (EUROAPS), validated the association between the triple aPL positivity and recurrent miscarriage (≥ 3 miscarriages <10 weeks) and fetal loss/stillbirth (>1 loss, over 10 weeks) (p=0.0505 and p=0.0033, respectively). Early-onset preeclampsia/HELLP and prematurity were associated with lupus anticoagulant positivity (p=0.0016 and p=0.0005, respectively), and FGR was associated to both triple aPL positivity and lupus anticoagulant positivity (p=0.0693 and p=0.0151 respectively) [2]. Additionally, Retz et al confirmed the triple aPL positivity as independent predictor of pregnancy loss by univariate and multivariate analysis (Crude Odd's Ratio 1.29) [44].…”
Section: Predictive Value Of Triple Apl Positivity and Presence Of Lumentioning
confidence: 95%
“…In the European Registry on Obstetric Antiphospholipid Syndrome (EUROAPS), a project by Alijotas-Reig et al the complement pathway of 201 women with obstetric antiphospholipid syndrome was analyzed: 98 women showed decreased values of complementemia, such as low C4 levels or low C3 levels or low C4 and C3 levels [2].…”
Section: Predictive Value Of Hypocomplementemiamentioning
confidence: 99%
See 1 more Smart Citation